Protective Effects of BDNF against C-Reactive Protein-Induced Inflammation in Women - Nicole Noren Hooten; Ngozi Ejiogu; Alan B. Zonderman; Michele K. Evans (Mediators of Inflammation)
Background. Since high sensitivity C-reactive protein (hsCRP) is predictive of cardiovascular events, it is important to examine the relationship between hsCRP and other inflammatory and oxidative stress markers linked to cardiovascular disease (CVD) etiology. Previously, we reported that hsCRP induces the oxidative stress adduct 8-oxo-7,8-dihydro-2′deoxyguanosine (8-oxodG) and that these markers are significantly associated in women. Recent data indicates that brain-derived neurotrophic factor (BDNF) may have a role in CVD. Methods and Results. We examined BDNF levels in 3 groups of women that were age- and race-matched with low (<3 mg/L), mid (>3–20 mg/L), and high (>20 mg/L) hsCRP (n=39 per group) and found a significant association between hsCRP, BDNF, and 8-oxodG. In African American females with high hsCRP, increases in BDNF were associated with decreased serum 8-oxodG. This was not the case in white women where high hsCRP was associated with high levels of BDNF and high levels of 8-oxodG. BDNF treatment of cells reduced CRP levels and inhibited CRP-induced DNA damage. Conclusion. We discovered an important relationship between hsCRP, 8-oxodG, and BDNF in women at hsCRP levels >3 mg/L. These data suggest that BDNF may have a protective role in counteracting the inflammatory effects of hsCRP.